Metode Analisis Dalam Menafsirkan al-Qur’an: Analisis Pada Tafsir al-Munir - Kgs. M. Choirul Muchlis; Kusnadi (Jurnal Cakrawala Akademika, 2024)
Research with the title "Analytical Methods in Interpreting the Qur'an in Tafsir Al-Munir." This research focuses on the systematics and methods of Tafsir Al-Munir. The book Tafsir Al-Munir Fi al-‘Aqidah wa al-Shariah wa al-Manhaj was compiled by Prof. Dr. Wahbah Zuhaili. A scholar, Islamic intellectual, and contemporary jurisprudence expert from Syria. He is widely recognized as one of the greatest authorities in the study of Islamic law in the modern era.In the book Tafsir Al-Munir, Wahbah al-Zuhaili groups the verses of the Qur'an according to the order of the mushaf and provides discussion titles that correspond to their themes. Explaining the general content of the surah, then discussing each verse from a linguistic perspective. Wahbah also mentions the authentic asbab al-nuzul and disregards weak narrations, followed by explanations of relevant stories. The verses being interpreted are presented in detail, followed by the derivation of the relevant laws. Finally, it discusses the literary aspects and i'rab of the verses. And also in the method used in the Tafsir al-Munir, starting from the sources of interpretation, the explanation method, the breadth of explanation, and the aspect of the  Ordely arrangement of verses